Revised Eighth Five Year Plan (1990-95) and Annual Plan (1991-92) of District Kargil - Planning Commission (Planning Commission, 1990)
The approved outlay for 7th five year plan of District Kargil was of the order of Rs. 4250.00 Lakhs and the actual expenditure of 7th five year plan is of the order of Rs. 5101.65 Lakhs. the revised 8th five year plan allocation has been fixed as Rs. 8554.00 Lakhs and the annual plan for 1991-92 has been drafted on the basis of 10% step up over the current year's approved plan allocation of Rs. 1253.00 Lakhs. Revenue component to the extent of Rs. 237.00 Lakhs of the schemes completed during 7th five year plan 1985-90 stands transferred to non-plan budget of 1990-91 as against the demand of Rs. 475.00 Lakhs.
Planning Section, Kargil